Structural Reforms in the Euro Area : Economic Impact and Role of Synchronization Across Markets and Countries - Everaert, Luc (IMF Working Papers; Working Paper, 2006)
Using the IMF's Global Economic Model, calibrated to the European Union, the effects of reform in product and labor markets are quantified for both a large and a small euro area economy. When markups in these markets are reduced, there are sizable long-term gains in output and employment. Most of these gains accrue to the reforming country regardless of whether reform takes place elsewhere; conversely, spillovers of reform elsewhere are limited. Labor and services market reforms have transitional costs as they induce a temporary decline in consumption, but raising competition in goods markets can mitigate some of these costs. Thus, coordinating the timing of reforms across markets is beneficial, and the more so the more open the reforming economy. In addition, synchronizing structural reforms across large countries of the euro area could eliminate transition costs. Increased supply would allow monetary policy to ease without jeopardizing price stability objectives, though in practice uncertainty may prevent full accommodation.